PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR IPA - Souisa, Haryo Franky; Malagifik, Agrice (LPPM Politeknik Saint Paul Sorong, 2024)
Fifth-grade students' interest in learning science varies. There were high, good, medium and low. However, their average interest in learning was still relatively low. This study aims to find out the role of teachers in increasing students' interest in learning, supporting and inhibiting factors, and how to overcome them. We conducted descriptive-qualitative research. Data was obtained through interviews, observations and questionnaires. Then, it was analyzed using the main phases of data analysis: data reduction, data display, and drawing conclusions. We found the role of teachers in increasing students' interest in learning, namely as educators, mentors, motivators, mediators, facilitators and evaluators. The supporting factors were educators, facilities and student conditions. Meanwhile, there were various inhibiting factors, namely lack of parental assistance and lack of appreciation for student achievement. Efforts to overcome these obstacles were by collaborating with teachers and parents and giving appreciation to students who excel. Keywords : Teacher’s role, interest in learning, science learning